Signifikansi Microteaching Pada Mata Kuliah Hubungan Masyarakat Dalam Meningkatkan Keterampilan Mengajar Mahasiswa Program Magister PAI di Universitas Sunan Giri Surabaya - Putro Suryonegoro; Muhammad Yusron Maulana El-Yunusi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Microteaching learning programs are considered to be very necessary in line with developments in the times that influence the mindset of students and society which is increasingly complex and difficult to control. Therefore, prospective teachers need to familiarize themselves with teaching practices to hone good classroom communication skills and manage classroom conditions through systematic field exercises. The MPAI Universitas Sunan Giri Surabaya Islamic Religious Education Master's Study Program is a higher education institution that pays attention to the importance of preparing professional prospective educators or teachers who are ready to face the challenges of the dynamic world of education. This research uses a qualitative descriptive method by collecting data through CAR Classroom Action Research observation research techniques or classroom action research which is directly carried out by educational practitioner teachers in the classroom to improve the learning process. The results of research using this method shows that implementing the microteaching program consistently and significantly can improve pedagogical skills, especially in the aspect of classroom management with a participatory audience and active and creative delivery of material by teachers. Thus, microteaching organized by the MPAI Unsuri study program must be maintained and developed into even better activities. It is hoped that this microteaching program will be an important focus for each element that has tasks, functions and joint contributions to maximize the goals of microteaching in all courses.